2022
DOI: 10.1186/s12934-022-01844-y
|View full text |Cite
|
Sign up to set email alerts
|

Polar mutagenesis of polycistronic bacterial transcriptional units using Cas12a

Abstract: Background Functionally related genes in bacteria are often organized and transcribed as polycistronic transcriptional units. Examples are the fim operon, which codes for biogenesis of type 1 fimbriae in Escherichia coli, and the atp operon, which codes for the FoF1 ATP synthase. We tested the hypothesis that markerless polar mutations could be efficiently engineered using CRISPR/Cas12a in these loci. Results Cas12a-mediated engineering of a termin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 56 publications
(94 reference statements)
3
2
0
Order By: Relevance
“…We did observe a significant effect on the levels of icsB transcription ( Fig. S4D ), particularly for the S. flexneri icsB ( Q32X ) mutant, which is consistent with our previous report ( 42 ) that some mutations, including premature stop codons, can decrease mRNA levels without affecting observed phenotypes. Altogether, these results showed that base-edited premature stop codon mutations did not result in any observable polar effects, at least at the phenotype level.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…We did observe a significant effect on the levels of icsB transcription ( Fig. S4D ), particularly for the S. flexneri icsB ( Q32X ) mutant, which is consistent with our previous report ( 42 ) that some mutations, including premature stop codons, can decrease mRNA levels without affecting observed phenotypes. Altogether, these results showed that base-edited premature stop codon mutations did not result in any observable polar effects, at least at the phenotype level.…”
Section: Resultssupporting
confidence: 92%
“…Total RNA extraction and qPCR were performed as previously described, with minor modifications ( 42 , 59 ). Bacteria were grown similarly to the mutagenesis experiment, but instead of spotting the dilutions, the cultures were treated with ice-cold stop solution (95% [vol/vol] ethanol, 5% [vol/vol] phenol, pH 4) for 30 min on ice.…”
Section: Methodsmentioning
confidence: 99%
“…We did observe a significant effect on the levels of icsB transcription (Supplementary Fig. S4D), particularly for the S. flexneri icsB(Q32X) mutant, which is consistent with our previous report (42) that some mutations, including premature STOP codons, can decrease mRNA levels without affecting observed phenotypes.…”
Section: Base Editing Results In Phenotypically Non-polar Mutationssupporting
confidence: 92%
“…We did observe a significant effect on the levels of icsB transcription (Supplementary Fig. S4D), particularly for the S. flexneri icsB(Q32X) mutant, which is consistent with our previous report (42) that some mutations, including premature STOP codons, can decrease mRNA levels without affecting observed phenotypes. Altogether, these results showed that base-edited premature STOP codon mutations did not result in any observable polar effects, at least at the phenotype level.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation